DIAGNOSTIC AND PROGNOSTIC VALUE OF SELENIUM AND SELENOPROTEIN P IN PATIENTS WITH COMORBID COURSE OF NON-ALCOHOLIC FATTY LIVER DISEASE AND ARTERIAL HYPERTENSION - Tverezovska, Iryna (Medicinski časopis, 2022)
Objective. To evaluate the diagnostic and prognostic value of selenoprotein P and selenium in the progression of liver damage in patients with NAFLD.Methods. The study involved 120 patients: 50 with isolated NAFLD, 50 - with comorbid NAFLD and hypertension, established according to the world and local guidelines. Liver function parameters, selenium and Selenoprotein P levels were assessed, and predictors of steatohepatitis were identified. Pearson's χ2, Mann-Whitney test, logistic regression were used.Results. The study found significant predominance of levels of Selenoprotein P (Sel P) and selenium in controls (71.0 [54.3; 76.1] ng/ml and 108.0 [96.9; 118.8] ng/ml respectively) compared with the NAFLD + hypertension (19.7 [8.0; 26.7] ng/ml and 43.5 (39.9; 49.1] ng/ml, p
Keywords: steatohepatitis; oxidative stress; comorbidity